Pyrexia of unknown origin: a rare presentation of primary ovarian lymphoma - Gokhale, Asha N.; Agarwal, Akriti; Purandare, Bharat D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
It is very rare to have a lymphomatous involvement of ovary. Malignant lymphoma of ovary is a well-known late manifestation of disseminated nodal disease. Primary ovarian lymphoma with ovarian mass as an initial manifestation is a rare entity and may have varied presentations which can cause confusion to the physician and cause delay in diagnosis. Study presents a case of non-Hodgkin’s lymphoma where the initial presentation was fever with weight loss, and was evaluated as pyrexia of unknown origin. When no other cause of fever was identified PET-CT was done showing metabolically active uterine mass with no lymphadenopathy. Exploratory laparotomy was planned followed by hysterectomy with bilateral salpingo ophorectomy with omentectomy. Ovarian malignancy was detected intraoperatively, which was diagnosed as diffuse large B cell lymphoma, NHL double expresser phenotype on histopathology and IHC. Patient was started on chemotherapy and is doing fine.